SAT0378 Autophagy is Up-Regulated in the Salivary Glands of Primary Sjogren's Syndrome Patients and Correlates with the Focus Score and Disease Activity. (9th June 2015) - Alessandri, C.; Ciccia, F.; Priori, R.; Astorri, E.; Guggino, G.; Alessandro, R.; Rizzo, A.; Conti, F.; Minniti, A.; Barbati, C.; Vomero, M.; Pendolino, M.; et al.
Abstract : Background: Autophagy is now considered as a major regulator in trafficking events that activates innate and adaptive immunity and consistent evidence supports its role in autoimmunity (1). Primary Sjogren's syndrome (pSS) is a systemic autoimmune disease characterized by infiltration of exocrine glands by T and B cells that, producing chemokines and cytokines, coordinate the chronic inflammatory process. No data on the role of autophagy in pSS are available in humans, although studies in mice demonstrated its involvement in the salivary and lacrimal gland homeostasis (2, 3). Objectives: We investigated the autophagy process in salivary gland tissue and in peripheral T lymphocytes from pSS patients to evaluate its possible implication in the pathogenesis of the disease. Methods: 30 patients with pSS, 20 patients with sicca syndrome or non-specific-chronic-sialoadenitis and 30 healthy donors were studied. Peripheral T lymphocytes were isolated by standard procedures. Salivary gland biopsies were evaluated by i) H&E to assess histological pattern, the severity of inflammatory infiltrate and the presence of germinal centers, ii) RT-PCR for the expression of autophagy-related genes and IL-23p19 and IL-21 mRNA. Autophagy-related proteins (LC3, Atg5, p62/SQSTM1) were detected in peripheral T lymphocytes by western blot and in salivary gland by immunohistochemistry and immunofluorescence. IL-21 and IL-23p19 serum levels were measured by ELISA. Results: Autophagy is up-regulated in T cells from the salivary glands, but not from the peripheral blood, of pSS patients and it is correlated with disease activity and damage indexes. Autophagy is also correlated with the local expression of the pro-inflammatory cytokines IL-21 and IL-23p19, but not with serum levels of these cytokines. Conclusions: Our data show that, in pSS, T cells present high levels of autophagy, which may up-regulate the expression of pro-inflammatory cytokines, providing evidence for a role of this process in the pathogenesis of pSS and identifying a possible therapeutic target. References: Pierdominici M, Vomero M, Barbati C et al. FASEB J. 2012; 26: 1400-1412. Morgan-Bathke M, Lin HH, Chibly AM et al. J Dent Res. 2013; 92: 911-917. Seo Y, Ji YW, Lee SM, et al. Cell Death Dis. 2014; 5: e1309. Disclosure of Interest: None declared